KUALITAS TIDUR PASIEN DIABETES MELLITUS TIPE 2 - Wiwit Febrina; Ratna Dewi; Wenny Lazdia; Rahmat Syukri; Putri Rahmadani; Lina Gusniati (LLDIKTI Wilayah X, 2023)
According to Riskesdas findings from 2018, the prevalence of Diabetes Mellitus in Indonesia increased to 2%. In 2019, Indonesia ranked seventh among the countries with the highest prevalence of diabetes, with a population of 10.7 million. The purpose of the study was to determine The Correlation Between Sleep Quality and Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus at Rasimah Ahmad Community Health Center, Bukitinggi in 2022.This study employed a descriptive analytic research design. In 2022, the population was all patients with diabetes Mellitus Type 2 at Rasimah Ahmad Community Health Center in Bukittinggi, with a total of 175 persons. Using an incidental sampling technique, 63 respondents who met the inclusion criteria were sampled. The study's findings revealed that 56 respondents with poor sleep quality were in the poor category, a majority of 52 respondents (92.9%) had high blood sugar levels (> 200 g/dl), and 7 respondents with good sleep were only slightly less than the same proportion of 3 respondents (42.9%) had a high blood glucose level (> 200 gr/dl). It is recommended that individuals with diabetes consult with healthcare professionals in order to assess the stability of their blood sugar levels and its impact on achieving appropriate sleep quality